Insider dan Outsider dalam Penerjemahan Al-Qur’an Di Jepang: Interaksi Otoritas Keagamaan dan Wacana Akademik - Nur Fadilah (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
Islam in Japan has developed as a minority religion through various channels, including migration, missionary efforts (da’wah), and academic engagement. One of the key aspects of this development is the translation of the Qur’an into Japanese. Two main categories of translators have played a significant role: Muslim insiders and non-Muslim outsiders. Outsider translators, such as Kenichi Sakamoto and Toshihiko Izutsu, adopted academic, linguistic, and political approaches in rendering the Qur’an, making their works widely appreciated in scholarly circles for their perceived objectivity and analytical rigor. In contrast, insider translators like Ryoichi Mita and Ko Nakata viewed translation as part of religious experience and da’wah, which led to greater acceptance within the local Muslim community. These differing approaches have shaped public reception: outsider translations are more commonly used in academic discourse, while insider versions are prevalent in religious practice. This study aims to analyze the methodological and ideological differences between these two groups in translating the Qur’an in Japan, and how each approach influences perceptions of Islam in Japanese society. Employing a qualitative literature-based method, the research examines various Qur’anic translations and community responses to them. The findings reveal that outsider translations contribute significantly to the intellectual understanding of Islam, while insider translations play a vital role in preserving the religious identity of Japan’s Muslim minority. Despite their differing orientations, both perspectives are crucial in shaping the image and understanding of Islam within contemporary Japanese society.